Alpha-Fe2O3-coated MIL-141 metal organic framework composite material as well as preparation method and application thereof
By using α-Fe2O3@MIL-141 metal-organic frame composite material, the problem of low utilization efficiency of active site when catalyzed degradation of polyethylene glycol is solved, efficient adsorption and catalytic degradation of PEG are achieved, and the characteristics of multiple utilization are provided, which is suitable for industrial applications.
Patent Information
- Application Number
- CN202510043651.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-15
AI Technical Summary
When existing single metal organic framework materials catalytically degrade polyethylene glycol, the active site utilization efficiency is low, the adsorption and catalytic degradation of PEG are insufficient, and the synergy of adsorption and catalytic degradation of PEG are not possible, and they cannot be reused.
The α-Fe2O3@MIL-141 metal-organic frame composite material is used, which forms a tight interface with the in-situ coated MIL-141 (Fe) through Ti-doped rod-shaped α-Fe2O3 nanoarray, improving catalytic activity and structural stability.
It realizes efficient adsorption and catalytic degradation of PEG, and the materials can be used multiple times after the reaction, reducing production costs and having good industrial application prospects.
Smart Images

Figure CN119819376A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalytic material preparation, and in particular to an α-Fe 2 O 3 @MIL-141 Metal-organic framework composite materials and their preparation methods and applications. Background Art
[0002] Polyethylene glycol (PEG) is a high molecular polymer with excellent water solubility, biocompatibility and chemical stability. Due to its unique properties, PEG is widely used as a drug carrier, solubilizer, lubricant, etc. in the medical field, as a moisturizer in the cosmetics industry, and is also commonly used as an additive for coatings, inks and other products in the industrial field. With the development of the global economy, the production and use of PEG has continued to grow. However, if the PEG waste after a large amount of use is not effectively treated, it will cause potential harm to the environment. Due to the high chemical stability of PEG, it is difficult to degrade quickly in the natural environment and is easily accumulated in environmental media such as soil and water. It may affect the ecological balance and have long-term and potential adverse effects on organisms, such as interfering with normal physiological processes in the body and affecting the structure of microbial communities.
[0003] At present, there are two main degradation methods for polyethylene glycol: chemical degradation and biological degradation. Although chemical degradation methods such as acid hydrolysis and alkaline hydrolysis can achieve the degradation of PEG to a certain extent, they often require harsh reaction conditions, such as high temperature, high pressure, strong acid or strong base environment, which not only consumes a lot of energy, but also easily produces a large amount of acid and alkali waste liquid, causing secondary pollution, and is difficult to apply in complex actual environmental systems. The biodegradation process is usually slow, and the degradation efficiency is limited by many factors, such as the type and activity of microorganisms, the specificity and stability of enzymes, etc., and the effect of biodegradation is often unsatisfactory.
[0004] Metal-organic frameworks (MOFs) are porous crystalline materials formed by self-assembly of metal ions or metal clusters and organic ligands through coordination bonds. MOFs have unique physical and chemical properties such as high specific surface area, adjustable pore size and pore structure, and abundant active sites. They have shown great application potential in many fields such as gas storage and separation, catalysis, and sensing. However, there are still some problems when single metal-organic framework materials are used for catalytic degradation of polyethylene glycol, such as low utilization efficiency of active sites, insufficient synergy of adsorption and catalytic degradation of PEG, and inability to be reused. Summary of the invention
[0005] In view of the problems that the utilization efficiency of active sites is low, the synergy of adsorption and catalytic degradation of PEG is insufficient, and the catalytic degradation of polyethylene glycol cannot be reused when a single metal organic framework material is used for catalytic degradation of polyethylene glycol in the prior art, the present invention provides an α-Fe 2 O 3 @MIL-141 Metal-organic framework composite materials and their preparation methods and applications.
[0006] In order to solve the above technical problems, the technical solution provided by the present invention is:
[0007] In a first aspect, the present invention provides an α-Fe 2 O 3 @MIL-141 Metal-organic framework composites, including Ti-doped rod-shaped α-Fe 2 O 3 A nanoarray and MIL-141(Fe) in situ coated on the surface of the nanoarray; wherein the organic ligand of the MIL-141(Fe) is tetrakis(4-carboxyphenyl)porphyrin.
[0008] Compared with the prior art, the metal framework organic material provided by the present invention has a rod-shaped α-Fe 2 O 3 Nanoarrays can provide a large specific surface area, which is conducive to the exposure of active sites. At the same time, the array structure can promote the transport of substances. Both the diffusion of reactants to the active sites of the catalyst and the detachment of reaction products can be carried out more efficiently. In addition, this array structure can also help to build an orderly electron transport channel, improve the electron transfer efficiency in the electrocatalytic process, and thus enhance the overall catalytic performance. Ti doping into α-Fe 2 O 3 The lattice will cause lattice distortion and produce more defect sites. These defect sites have high chemical activity and can serve as additional active centers in the electrocatalytic process to adsorb reactant molecules and promote the reaction. 2 O 3 The MIL-141(Fe) on the surface of the nanoarray can further increase the specific surface area of the material. Its own porosity can provide more reaction sites for the catalytic reaction, making the reactant molecules more easily adsorbed and activated; α-Fe 2 O 3 The nanoarray forms a close interfacial contact with MIL-141(Fe), and this interfacial interaction is conducive to the transfer and redistribution of charges between the two, promoting the efficient electrocatalytic reaction.
[0009] In addition, Ti-doped rod-shaped α-Fe 2 O 3The nanoarray has good structural stability, which enables the nanoarray to maintain its structural integrity in the complex environment of catalytic reaction. The coating of MIL-141(Fe) further enhances the stability of the material. The structure of its organic ligands and metal nodes can 2 O 3 The nanoarray plays a certain protective role, preventing it from agglomerating or structurally destroying during a long catalytic process. In the composite material provided by the present invention, the Fe site in MIL-141(Fe), the Ti-doped α-F 2 O 3 Ti site and F 2 O 3 The lattice oxygen has a synergistic catalytic effect and can maintain relatively stable performance during multiple catalytic cycles, which has broad application prospects in the field of industrial electrocatalysis.
[0010] In a second aspect, the present invention provides an α-Fe 2 O 3 @MIL-141 A method for preparing a metal organic framework composite material, the preparation method comprising the following steps:
[0011] Step a, adding a soluble iron salt to an aqueous sodium sulfate solution, mixing evenly, to obtain a ferric chloride mixed solution;
[0012] Add soluble titanium salt into anhydrous ethanol and mix well to obtain titanium chloride solution;
[0013] Evenly mixing the ferric chloride mixed solution and the titanium chloride solution to obtain a precursor solution;
[0014] Step b, adding the precursor solution and conductive glass into a hydrothermal reactor, reacting at 110° C. to 130° C. to form a Fe-OOH nanoarray on the conductive glass; calcining the Fe-OOH nanoarray at 400° C. to 500° C. to obtain Fe 2 O 3 Nanoarrays;
[0015] Step c, dissolving tetrakis(4-carboxyphenyl)porphyrin in N,N-dimethylformamide, adding trifluoroacetic acid, and mixing well to obtain a tetrakis(4-carboxyphenyl)porphyrin solution;
[0016] Step d, the Fe 2 O 3 The nanoarray and tetrakis(4-carboxyphenyl)porphyrin solution were added into a hydrothermal reactor and reacted at 160℃~180℃ to obtain α-Fe 2 O 3 @MIL-141 Metal-organic framework composites.
[0017] Compared with the prior art, the α-Fe 2 O 3 @MIL-141 The preparation method of metal organic framework composite material has the following advantages:
[0018] The present invention selects Fe-OOH nanoarray as a precursor to prepare Fe 2 O 3 Nanoarrays are beneficial for obtaining nanoarrays with uniform size, and the Fe 2 O 3 Nanoarrays have unique interface structures. During the transformation process, the Fe 2 O 3 There is a special interface interaction between the incompletely converted Fe-OOH and other intermediate phases. This interface structure helps to improve the stability and activity of the material. 2 O 3 Ti was in situ doped during the process to further improve the activity and structural stability of the nanoarray. Furthermore, Fe was etched by trifluoroacetic acid using a hydrothermal method. 2 O 3 , so that the etched Fe 3+ It reacts with tetrakis(4-carboxyphenyl)porphyrin (TCPP) ligand to form Fe 2 O 3 The surface is in-situ coated with MIL-141(Fe) to form a stable core-shell structure, which improves the overall stability of the material and reduces the interaction between MIL-141 and Fe during use. 2 O 3 The separation between them can better maintain the performance of the material. At the same time, the in-situ reaction can realize the separation of MIL-141 on Fe 2 O 3 The uniform coating of the surface is conducive to the precise control of the thickness and uniformity of the coating layer. The uniform coating layer can provide a more consistent distribution of active sites, thereby improving the catalytic efficiency. In addition, the coating of MIL-141 can protect the Fe 2 O 3 active sites to prevent them from being poisoned or inactivated during the reaction, thereby improving stability while maintaining good activity and extending the service life of the material.
[0019] The α-Fe prepared by the present invention 2 O 3@MIL-141 metal organic framework composite material not only has high catalytic activity, but also has high adsorption capacity for organic pollutants. It can enrich and store a large number of organic pollutant molecules, achieving the synergy of adsorption and catalytic degradation. When the adsorbed organic pollutant molecules react, under the action of concentration gradient and electrostatic attraction, the adsorbed unreacted organic pollutant molecules can spontaneously migrate to the α-Fe 2 O 3 @MIL-141 metal organic framework composite material active site, so that the electrocatalytic reaction continues to proceed efficiently, and the α-Fe 2 O 3 @MIL-141 metal-organic framework composite materials can be used multiple times, effectively reducing production costs and having high prospects for industrial application.
[0020] It should be noted that the tetrakis(4-carboxyphenyl)porphyrin (TCPP) described in the present invention can be prepared using a commercially available product or a conventional method in the art.
[0021] As a specific embodiment of the present invention, the preparation method of tetrakis(4-carboxyphenyl)porphyrin (TCPP) comprises the following steps:
[0022] Take 6.5-8.5g of methyl paraformylbenzoate and 3-5mL of pyrrole, add them to 100-120mL of propionic acid, and dissolve them by ultrasonication to obtain solution A; add solution A to a three-necked flask, control the oil bath temperature to 150-160°C, and carry out condensation reflux reaction for 12-14h under nitrogen atmosphere. After the reaction is completed, cool, vacuum filter, wash the filter cake with anhydrous ethanol, ethyl acetate and tetrahydrofuran in turn, and vacuum dry to obtain a purple solid. Add the obtained solid to 20-30mL of 45-55mM KOH aqueous solution, and ultrasonicate to obtain solution B; add solution B to a round-bottom flask, control the oil bath temperature to 80-90°C, and continue heating to react for 12-14h. After the reaction is completed, the reaction solution is rotary evaporated, and the solution pH is adjusted to 6 using a pH=1 HCl solution, and the acid-adjusted solution is rinsed with deionized water, and vacuum dried to obtain tetrakis(4-carboxyphenyl)porphyrin (TCPP).
[0023] Preferably, in step a, the soluble iron salt is ferric chloride.
[0024] Preferably, in step a, the molar ratio of the soluble iron salt to sodium sulfate is (0.5-2):(0.5-2). Preferably, the molar ratio of the soluble iron salt to sodium sulfate is 1:1.
[0025] Preferably, in step a, the ratio of sodium sulfate to water in the sodium sulfate aqueous solution is (0.5-2) mmol: (8-12) mL. Preferably, the ratio of sodium sulfate to water in the sodium sulfate aqueous solution is 1 mmol: 10 mL.
[0026] The preferred concentration and addition ratio of the sodium sulfate aqueous solution can promote the rapid dissolution of ferric chloride, thereby facilitating the full progress of the subsequent hydrothermal reaction.
[0027] Preferably, in step a, the soluble titanium salt is titanium tetrachloride.
[0028] Preferably, in step a, the ratio of the soluble titanium salt to anhydrous ethanol is (0.5-2) mmol: (15-25) mL. Preferably, the ratio of the soluble titanium salt to anhydrous ethanol is (1.5-2) mmol: 20 mL.
[0029] Preferably, in step a, the molar ratio of the soluble titanium salt to the soluble iron salt is (0.5-2):(0.5-2).
[0030] Preferably, in step a, the volume ratio of the ferric chloride mixed solution to the titanium chloride solution is 1:(40-50).
[0031] Preferred TiCl 4 The concentration and doping amount can improve the prepared α-Fe 2 O 3 catalytic activity and structural stability.
[0032] Preferably, in step b, the reaction time is 4 h to 5 h.
[0033] The optimal reaction temperature and reaction time can improve the morphology uniformity of the Fe-OOH nanoarray.
[0034] Preferably, in step b, the calcination time is 2h to 3h.
[0035] The optimal calcination temperature and time can transform Fe-OOH nanoarrays into α-Fe with good crystallinity under appropriate conditions. 2 O 3 Nanoarrays, and the purity of the product is relatively high, reducing the presence of impurity phases, which is beneficial to improving the performance and stability of the material, enabling it to play a better role in optoelectronics, catalysis and other fields.
[0036] As an embodiment of the present invention, the conductive glass is FTO glass. Before use, the FTO glass is cleaned with detergent, then soaked in 10 mL of toluene, acetone, anhydrous ethanol and deionized water in sequence, and ultrasonically cleaned respectively to ensure the cleanliness of the FTO glass surface.
[0037] Preferably, in step c, the ratio of the tetrakis(4-carboxyphenyl)porphyrin solution to N,N-dimethylformamide is (0.04-0.06) mol: (15-25) mL.
[0038] Preferably, in step c, the volume ratio of N,N-dimethylformamide to trifluoroacetic acid is (15-25):(0.4-0.6).
[0039] Preferably, in step d, the reaction time is 12 h to 14 h.
[0040] The optimal reaction conditions can achieve the MIL-141 in α-Fe 2 O 3 The uniform coating of the nanoarray surface produces a stable α-Fe 2 O 3 @MIL-141 core-shell structure nanomaterials.
[0041] In a third aspect, the present invention also provides the above-mentioned α-Fe 2 O 3 @MIL-141 Application of metal-organic framework composites in photoelectrocatalytic degradation of polyethylene glycol.
[0042] Ti doping can adjust the α-Fe 2 O 3 The energy band structure of MIL-141(Fe) is conducive to more fully utilizing the energy of visible light sources such as sunlight and improving the efficiency of photocatalytic reactions. At the same time, the doping of Ti can effectively inhibit the recombination of photogenerated carriers. The one-dimensional structure of the rod-shaped nanoarray provides a shorter diffusion path for photogenerated carriers, which is conducive to the rapid transmission of carriers to the catalyst surface to react with polyethylene glycol molecules. At the same time, the porous structure of MIL-141(Fe) can also serve as a carrier transmission channel, further accelerating the charge transmission speed, improving the kinetics of the photoelectrocatalytic reaction, and enabling the degradation reaction of polyethylene glycol to proceed more rapidly. In addition, MIL-141(Fe) and α-Fe 2 O 3 The heterojunction formed between them also helps to promote the transfer of photogenerated carriers between them, further reducing the recombination probability of carriers, improving the charge separation efficiency, and allowing more photogenerated electrons and holes to participate in the degradation reaction of polyethylene glycol. 2 O 3 The synergistic effect between the two effectively improves the degradation performance of the composite material to polyethylene glycol. At the same time, the composite material can be reused many times, reducing the cost of treating polyethylene glycol pollution and has good practical application prospects.
[0043] In a fourth aspect, the present invention also provides a method for photoelectrocatalytic degradation of polyethylene glycol, comprising the following steps:
[0044] In a three-electrode system, any of the above-mentioned α-Fe 2 O 3 @MIL-141 Preparation method of metal organic framework composite material 2 O 3 @MIL-141 metal-organic framework composite material is used as the working electrode to carry out photoelectrocatalytic degradation of solutions containing polyethylene glycol.
[0045] Furthermore, the current density of the photoelectrocatalytic degradation is 4 mA / cm 2 ~6mA / cm 2 .
[0046] Furthermore, the photoelectrocatalytic degradation process uses a xenon lamp for illumination, the current of the xenon lamp is 15A to 20A, and the filter is 420nm.
[0047] The α-Fe prepared by the present invention 2 O 3 @MIL-141 metal organic framework composite material is a new type of MOF material with a core-shell structure. It can efficiently degrade polyethylene glycol by combining adsorption and photoelectrocatalysis, greatly improving the reaction efficiency. At the same time, it has good stability, simple preparation method, easy-to-obtain materials, catalysts that can be recycled multiple times, and low energy consumption. It has high industrial promotion value in the field of wastewater treatment technology containing polyethylene glycol. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 The α-Fe prepared in Example 4 2 O 3 X-ray diffraction (XRD) patterns of nanoarray and MOF (141)-450 composites;
[0049] Figure 2 The α-Fe prepared in Example 4 2 O 3 Scanning electron microscopy images and micro-area elemental analysis images of nanoarray and MOF(141)-450 composite materials, where (a) α-Fe 2 O 3 Nanoarray, (b) to (c) are scanning electron microscopy images of MOF(141)-450 at different magnifications, and (d) to (g) are EDS elemental analysis images;
[0050] Figure 3 This is a transmission electron microscopy image of the MOF (141)-450 composite material prepared in Example 4;
[0051] Figure 4 The α-Fe prepared in Example 4 2 O 3 XPS spectra of nanoarrays and MOF(141)-450 composites, including (a) total spectrum, (b) C1s, (c) O1s, (d) Fe2p, (e) N1s, and (f) XPS valence band spectrum;
[0052] Figure 5 This is the LSV diagram of the MOF(141)-450 composite material prepared in Example 4;
[0053] Figure 6 The impedance diagram of the MOF (141)-450 composite material prepared in Example 4;
[0054] Figure 7 This is a graph showing the degradation efficiency of the MOF (141)-450 composite material prepared in Example 4 for photoelectric degradation of polyethylene glycol;
[0055] Figure 8 This is a cyclic stability diagram of the photoelectric degradation of polyethylene glycol by the MOF(141)-450 composite material prepared in Example 4. DETAILED DESCRIPTION
[0056] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0057] In order to better illustrate the present invention, further examples are given below.
[0058] The preparation method of tetrakis(4-carboxyphenyl)porphyrin (TCPP) used in the following examples comprises the following steps:
[0059] Take 6.9g of methyl paraformylbenzoate and 3mL of pyrrole, add them to 100mL of propionic acid, and dissolve them by ultrasonication to obtain solution A; add solution A to a three-necked flask, control the oil bath temperature to 155℃, and carry out condensation reflux reaction for 12h under nitrogen atmosphere. After the reaction is completed, cool, vacuum filter, wash the filter cake with anhydrous ethanol, ethyl acetate and tetrahydrofuran in turn until the filtrate is colorless, and vacuum dry to obtain a purple solid. Add the obtained solid to 25mL of 46.95mM KOH aqueous solution, ultrasonicate to obtain solution B; add solution B to a round-bottom flask, control the oil bath temperature to 80℃, and continue heating to react for 12h. After the reaction is completed, the reaction solution is rotary evaporated until no liquid flows out of the condenser tube, and the solution pH is adjusted to 6 with a pH=1 HCl solution, and the acid-adjusted solution is rinsed with deionized water, and vacuum dried to obtain tetrakis(4-carboxyphenyl)porphyrin (TCPP).
[0060] Other conditions defined in the present invention may also be used to prepare tetrakis(4-carboxyphenyl)porphyrin (TCPP), as long as they are within the conditions defined in the present invention. The following examples and comparative examples may also use commercially available tetrakis(4-carboxyphenyl)porphyrin (TCPP).
[0061] The FTO glass used in the following examples and comparative examples has a size of 3 cm*1 cm. It is cleaned with detergent before use, and then ultrasonically cleaned in 10 mL of toluene, acetone, anhydrous ethanol and deionized water for 30 min respectively to obtain clean FTO glass.
[0062] Example 1
[0063] This embodiment provides an α-Fe 2 O 3 The preparation method of @MIL-141 metal organic framework composite material comprises the following steps:
[0064] Step 1: Take 1mmol Na 2 SO 4 Add 10 mL of deionized water and dissolve by ultrasonic to obtain Na 2 SO 4 Solution; take 1mmol FeCl 3 6H 2 O was added to the prepared Na 2 SO 4 The solution was dissolved by ultrasonication to obtain solution A;
[0065] Use a pipette to pipette 2 mmol of TiCl 4 , and quickly drip into 20 mL of anhydrous ethanol, dissolve by ultrasonication to obtain solution B;
[0066] According to the volume ratio of solution A to solution B of 1:40, solution B was pipetted with a dropper, and slowly dripped into solution A under stirring, and ultrasonically dispersed to obtain solution C;
[0067] Step 2: Use a dropper to transfer 5 mL of solution C, add it into a high-pressure reactor, and insert a clean FTO glass into the bottom of the reactor, react at 115°C for 4 hours, cool and heat to room temperature, take out the FTO glass, wash the surface with anhydrous ethanol and deionized water, and vacuum dry to obtain Fe-OOH nanoarrays;
[0068] Step 3: Place the sample prepared in step 2 into a tube furnace and anneal it in air. Adjust the annealing temperature of the tube furnace to 450°C, keep it warm for 2 hours, and cool it to room temperature to obtain α-Fe 2 O 3 -450 nanorod array, light brick red;
[0069] Step 4: Take 0.05 mmol tetrakis (4-carboxyphenyl) porphyrin (TCPP), add it to 20 mL of N, N-dimethylformamide, dissolve it by ultrasonic, add 0.5 mL of trifluoroacetic acid, mix it by ultrasonic, and obtain TCPP solution; put the surface growth α-Fe prepared in step 3 into the autoclave 2 O 3 -450 nanorod array FTO glass, add 5mL TCPP solution, react at 160℃ for 12h, cool to room temperature, take out the sample, put it into a container filled with N,N-dimethylformamide and acetone, soak for 10min respectively, and vacuum dry to obtain α-Fe 2 O 3 @MIL-141 metal organic framework composite material, denoted as MOF(141)-450.
[0070] Take 130mL Na 2 SO 4 , polyethylene glycol (PEG) mixed solution, wherein Na 2 SO 4 The concentration was 0.05M, and the concentration of PEG was 10mg / L. The platinum electrode was used as the counter electrode, the saturated Ag / AgCl electrode was used as the reference electrode, and the 3*1cm 2 The MOF (141)-450 thin film glass was used as the working electrode. At pH = 5, the current density was 5 mA / cm 2 The catalytic activity was tested under the conditions of xenon lamp (current 16A, filter 420nm). The experimental results showed that the degradation efficiency of the product on PEG solution was 92.3% within 4 hours.
[0071] Example 2
[0072] This embodiment provides an α-Fe 2 O3 The preparation method of @MIL-141 metal organic framework composite material comprises the following steps:
[0073] Step 1: Take 0.5mmol Na 2 SO 4 Add 8 mL of deionized water and dissolve by ultrasonic to obtain Na 2 SO 4 Solution; take 2mmol FeCl 3 6H 2 O was added to the prepared Na 2 SO 4 The solution was dissolved by ultrasonication to obtain solution A;
[0074] Use a pipette to pipette 1 mmol of TiCl 4 , and quickly drip into 25 mL of anhydrous ethanol, dissolve by ultrasonication to obtain solution B;
[0075] According to the volume ratio of solution A to solution B of 1:40, solution B was pipetted with a dropper, and slowly dripped into solution A under stirring, and ultrasonically dispersed to obtain solution C;
[0076] Step 2: Use a dropper to transfer 5 mL of solution C, add it into a high-pressure reactor, and insert a clean FTO glass into the bottom of the reactor, react at 110°C for 5 h, cool and heat to room temperature, take out the FTO glass, wash the surface with anhydrous ethanol and deionized water, and vacuum dry to obtain Fe-OOH nanoarrays;
[0077] Step 3: Place the sample prepared in step 2 into a tube furnace and anneal it in air. Adjust the annealing temperature of the tube furnace to 400°C, keep it warm for 3 hours, and cool it to room temperature to obtain α-Fe 2 O 3 -450 nanorod array, light brick red;
[0078] Step 4: Take 0.06 mmol tetrakis (4-carboxyphenyl) porphyrin (TCPP), add it to 25 mL of N, N-dimethylformamide, dissolve it by ultrasonic, add 0.6 mL of trifluoroacetic acid, mix it by ultrasonic, and obtain TCPP solution; put the surface growth α-Fe prepared in step 3 into the autoclave 2 O 3 -450 nanorod array FTO glass, add 5mL TCPP solution, react at 170℃ for 12h, cool to room temperature, take out the sample, put it into a container filled with N,N-dimethylformamide and acetone, soak for 10min respectively, and vacuum dry to obtain α-Fe 2 O 3 @MIL-141 metal organic framework composite material, denoted as MOF(141)-450.
[0079] Take 130mL Na 2 SO 4 , polyethylene glycol (PEG) mixed solution, wherein Na 2 SO 4 The concentration is 0.05M, and the concentration of PEG is 10mg / L. The platinum electrode is used as the counter electrode, the saturated Ag / AgCl electrode is used as the reference electrode, and the 3*1cm 2 The MOF (141)-450 thin film glass was used as the working electrode. At pH = 5, the current density was 5 mA / cm 2 The catalytic activity was tested under the conditions of xenon lamp (current 16A, filter 420nm). The experimental results showed that the degradation efficiency of the product on PEG solution was 91.6% within 4 hours.
[0080] Example 3
[0081] This embodiment provides an α-Fe 2 O 3 The preparation method of @MIL-141 metal organic framework composite material comprises the following steps:
[0082] Step 1: Take 2mmol Na 2 SO 4 Add 12 mL of deionized water and dissolve by ultrasonic to obtain Na 2 SO 4 Solution; take 0.5mmol FeCl 3 6H 2 O was added to the prepared Na 2 SO 4 The solution was dissolved by ultrasonication to obtain solution A;
[0083] Use a pipette to pipette 0.5 mmol of TiCl 4 , and quickly drip into 15 mL of anhydrous ethanol, dissolve by ultrasonication to obtain solution B;
[0084] According to the volume ratio of solution A to solution B of 1:50, solution B was pipetted with a dropper, and slowly dripped into solution A under stirring, and ultrasonically dispersed to obtain solution C;
[0085] Step 2: Use a dropper to transfer 5 mL of solution C, add it into a high-pressure reactor, and insert a clean FTO glass into the bottom of the reactor, react at 120°C for 4 hours, cool and heat to room temperature, take out the FTO glass, wash the surface with anhydrous ethanol and deionized water, and vacuum dry to obtain Fe-OOH nanoarrays;
[0086] Step 3: Place the sample prepared in step 2 into a tube furnace and anneal it in air. Adjust the annealing temperature of the tube furnace to 500°C, keep it warm for 2 hours, and cool it to room temperature to obtain α-Fe2 O 3 -450 nanorod array, light brick red;
[0087] Step 4: Take 0.04 mmol tetrakis (4-carboxyphenyl) porphyrin (TCPP), add it to 15 mL of N, N-dimethylformamide, dissolve it by ultrasonic, add 0.4 mL of trifluoroacetic acid, mix it by ultrasonic, and obtain TCPP solution; put the surface growth α-Fe prepared in step 3 into the autoclave 2 O 3 -450 nanorod array FTO glass, add 5mL TCPP solution, react at 180℃ for 12h, cool to room temperature, take out the sample, put it into a container filled with N,N-dimethylformamide and acetone, soak for 10min respectively, and vacuum dry to obtain α-Fe 2 O 3 @MIL-141 metal organic framework composite material, denoted as MOF(141)-450.
[0088] Take 130mL Na 2 SO 4 , polyethylene glycol (PEG) mixed solution, wherein Na 2 SO 4 The concentration was 0.05M, and the concentration of PEG was 10mg / L. The platinum electrode was used as the counter electrode, the saturated Ag / AgCl electrode was used as the reference electrode, and the 3*1cm 2 The MOF (141)-450 thin film glass was used as the working electrode. At pH = 5, the current density was 5 mA / cm 2 The catalytic activity was tested under the conditions of xenon lamp (current 16A, filter 420nm). The experimental results showed that the degradation efficiency of the product on PEG solution was 91.3% within 4 hours.
[0089] Example 4
[0090] This embodiment provides an α-Fe 2 O 3 The preparation method of @MIL-141 metal organic framework composite material comprises the following steps:
[0091] Step 1: Take 1mmol Na 2 SO 4 Add 10 mL of deionized water and dissolve by ultrasonic to obtain Na 2 SO 4 Solution; take 1mmol FeCl 3 6H 2 O was added to the prepared Na 2 SO 4 The solution was dissolved by ultrasonication to obtain solution A;
[0092] Use a pipette to pipette 2 mmol of TiCl 4 , and quickly drip into 20 mL of anhydrous ethanol, dissolve by ultrasonication to obtain solution B;
[0093] According to the volume ratio of solution A to solution B of 1:45, solution B was pipetted with a dropper, and slowly dripped into solution A under stirring, and ultrasonically dispersed to obtain solution C;
[0094] Step 2: Use a dropper to transfer 5 mL of solution C, add it into a high-pressure reactor, and insert a clean FTO glass into the bottom of the reactor, react at 120°C for 4 hours, cool and heat to room temperature, take out the FTO glass, wash the surface with anhydrous ethanol and deionized water, and vacuum dry to obtain Fe-OOH nanoarrays;
[0095] Step 3: Place the sample prepared in step 2 into a tube furnace and anneal it in air. Adjust the annealing temperature of the tube furnace to 450°C, keep it warm for 2 hours, and cool it to room temperature to obtain α-Fe 2 O 3 -450 nanorod array, light brick red;
[0096] Step 4: Take 0.05 mmol tetrakis (4-carboxyphenyl) porphyrin (TCPP), add it to 20 mL of N, N-dimethylformamide, dissolve it by ultrasonic, add 0.5 mL of trifluoroacetic acid, mix it by ultrasonic, and obtain TCPP solution; put the surface growth α-Fe prepared in step 3 into the autoclave 2 O 3 -450 nanorod array FTO glass, add 5mL TCPP solution, react at 160℃ for 12h, cool to room temperature, take out the sample, put it into a container filled with N,N-dimethylformamide and acetone, soak for 10min respectively, and vacuum dry to obtain α-Fe 2 O 3 @MIL-141 metal organic framework composite material, denoted as MOF(141)-450.
[0097] Characterization
[0098] Figure 1 The α-Fe prepared in this example 2 O 3 X-ray diffraction patterns of the MOF(141)-450 nanorod array and the MOF(141)-450 composite material. It can be seen from the figure that the MOF(141)-450 composite material formed in situ by trifluoroacetic acid etching shows α-Fe 2 O 3The unique characteristic peaks indicate that the MOF(141)-450 composite material has not changed its original crystal structure. However, the MOF(141)-450 composite sample does not show the characteristic peaks belonging to MIL-141. The reason may be that during the preparation of the composite material, Fe 3+ Very little, resulting in too low content of MIL-141, or low crystallinity of the coated MIL-141, resulting in insufficient diffraction peak of MIL-141 to appear within 15° in the figure.
[0099] Figure 2 The α-Fe prepared in this example 2 O 3 SEM and EDS images of -450 nanorod arrays and MOF(141)-450 composites. Figure 2 (a) is α-Fe 2 O 3 -450 SEM image, Figure 2 (b) and Figure 2 (c) is the SEM image of the MOF(141)-450 composite material at different magnifications. It can be seen that the nanorods of the MOF(141)-450 composite material are smaller than those of the α-Fe 2 O 3 -450 diameter becomes thicker, the length of the nanorods of the MOF(141)-450 composite material is about 1 μm and the diameter is about 30 nm. Figure 2 (d) to (e) are EDS images of MOF(141)-450 composites. It can be seen from the figures that MOF(141)-450 composites contain four elements: C, N, O, and Fe. Among them, the N element mainly comes from TCPP, the ligand of MIL-141. This further proves that MIL-141 has a strong affinity for α-Fe 2 O 3 Successful growth on nanorods.
[0100] Figure 3 This is a transmission electron micrograph of the MOF(141)-450 composite material prepared in this example. It can be seen from the figure that α-Fe 2 O 3 The outside of the nanorods is evenly coated with a layer of MOFs, presenting a typical core-shell structure.
[0101] Figure 4 The α-Fe prepared in this example 2 O 3 XPS graph of -450 and MOF(141)-450 composite material. Figure 4 In the overall spectrum (a), it is observed that α-Fe 2 O 3-450, the peaks of C1s, O 1s, and Fe 2p appear, indicating that α-Fe 2 O 3 In addition to the above elements, the N1s peak also appeared in the full spectrum of the MOF(141)-450 composite material, proving that α-Fe 2 O 3 There is a thin layer of MIL-141 on the surface. Figure 4 (b) is the spectrum of C1s, in α-Fe 2 O 3 -450 observed binding energies of 284.8eV, 286.44eV, and 288.8eV, corresponding to CC, CO, and C=O characteristic peaks, respectively. This may be due to the fact that in the preparation of α-Fe 2 O 3 -450 process or its surface adsorption pollution caused by air carbon pollution. In MOF (141) -450, characteristic peaks with binding energies of 286.24 eV and 288.41 eV appeared, corresponding to the binding energies of CN and OC = O in MIL-141. This shows that the organic ligand TCPP has successfully bound to α-Fe 2 O 3 Forming MIL-141. Figure 4 (c) is the spectrum of O1s, in α-Fe 2 O 3 -450, the binding energies of 529.98 eV and 1.74 eV were observed, corresponding to the characteristic peaks of Fe-O and OVS, respectively. In MOF(101)-450, the binding energies of 529.95 eV and 531.47 eV were observed, corresponding to the characteristic peaks of Fe-O and C=O, respectively. 2 O 3 Compared with the Fe-O peak, the binding energy of the Fe-O characteristic peak shifts, which indicates that α-Fe 2 O 3 There is electron transfer or charge transfer between -450 and MOF(141)-450. In addition, Figure 4 (d) is the Fe 2p spectrum. 2 O 3 The two main peaks at binding energies of 710.89 eV and 724.02 eV in -450 correspond to Fe 2p3 / 2 and Fe 2p1 / 2, respectively. 2 O 3 Compared with the pure sample of MOF(141)-450, the binding energies of the two main peaks in MOF(141)-450 are at 710.87 eV and 723.99 eV, and the shift in binding energy may be caused by the increase in the outer electron cloud density and the increase in shielding effect. Figure 4(e) is the N 1s spectrum, α-Fe 2 O 3 The presence of N element was not observed in the pure MOF(141)-450 sample, while XPS analysis of the MOF(141)-450 composite sample showed characteristic peaks at 398.7 eV, 400.03 eV, and 401.93 eV, corresponding to Fe-N, CN, and -NH 2 , which further confirms the existence of MIL-141 shell in the composite material. Figure 4 As shown in (f), α-Fe 2 O 3 The valence bands of MOF(141)-450 and MOF(141)-450 composite catalysts are 1.46eV and 1.29eV, respectively.
[0102] Photoelectric performance test
[0103] The photoelectrocatalytic performance of the samples was tested using a Shanghai Chenhua CHI760 electrochemical workstation in a standard three-electrode system. 2 The MOF (141) -450 thin film glass was used as the working electrode, the counter electrode was a platinum electrode, the reference electrode was a Hg / HgO electrode, and the electrolyte was 100 mL of 0.5 M anhydrous sodium sulfate solution. A 300 W xenon lamp light source system and an AM 1.5G filter were used to simulate sunlight irradiation, and the samples were subjected to linear sweep voltammetry (LSV) and electrochemical impedance spectroscopy (EIS) tests, such as Figure 5 and Figure 6 The experimental results show that the current density of the product is -0.43mA·cm when the applied voltage is -0.7V. -2 , is the α-Fe prepared in step 3 2 O 3 -450 nm arrays produced 1.25 times the current, with significantly enhanced optoelectronic performance.
[0104] Performance of photoelectrocatalytic degradation of polyethylene glycol
[0105] Take 130mL Na 2 SO 4 , polyethylene glycol (PEG) mixed solution, wherein Na 2 SO 4 The concentration is 0.05M, and the concentration of PEG is 10mg / L. The platinum electrode is used as the counter electrode, the saturated Ag / AgCl electrode is used as the reference electrode, and the 3*1cm 2 The MOF (141)-450 thin film glass was used as the working electrode. At pH = 5, the current density was 5 mA / cm 2The catalytic activity was tested under the conditions of xenon lamp (current 16A, filter 420nm). The experimental results showed that the degradation efficiency of the product for PEG solution was 93.1% within 4 hours. 2 O 3 -450 nanometer array was used as the working electrode. The test was carried out according to the above method. The degradation efficiency of PEG solution was 49.8% within 4 hours. Compared with α-Fe 2 O 3 -450 nanoarray, the degradation rate of polyethylene glycol by MOF (141)-450 increased by 43.3%. The degradation process comparison is shown in Figure 7.
[0106] In order to further explore the stability performance of the MOF (141) -450 composite material prepared in the example, the MOF (141) -450 composite material prepared in this example was subjected to three cyclic degradation tests of PEG according to the same method as above. Figure 8 As shown in the figure, the degradation efficiency of the first photocatalytic degradation experiment was 93.1%, the degradation efficiency of the second photocatalytic degradation experiment was 90.7%, and the third was 89.9%. Therefore, the cyclic experiment proves that the degradation efficiency of the MOF (141) -450 composite material only decreased slightly after three consecutive cyclic degradation experiments, and it has good catalyst stability.
[0107] Comparative Example 1
[0108] This comparative example provides an α-Fe 2 O 3 @MIL-141 Preparation method of metal organic framework composite material, the only difference from Example 4 is that Fe-TCPP is directly used with surface grown α-Fe 2 O 3 -450 nanorod array FTO glass was reacted, the specific steps are as follows:
[0109] Steps 1 to 3 are exactly the same as those in Example 4;
[0110] Step 4: Take 6.9 g of methyl p-formylbenzoate and 20 mL of pyrrole, add them to 100 mL of propionic acid in turn, dissolve them by ultrasonication, and obtain solution A; add solution A to a three-necked flask, control the oil bath temperature to 155 ° C, and carry out condensation reflux reaction for 12 hours under a nitrogen atmosphere. After the reaction is completed, cool, vacuum filter, and dry to obtain TPP-COOMe; 0.854 g of TPP-COOMe and 2.5 g of 128 mM FeCl 2 ·4H 2The O solution was added to 100 mL of N,N-dimethylformamide and refluxed for 6 h. The mixture was cooled to room temperature, 150 mL of water was added, filtered, and washed twice with 50 mL of water. The obtained solid was dissolved in chloroform, then washed three times with 1 M HCl, and washed twice with water. The organic layer was dried over anhydrous magnesium sulfate and evaporated. The obtained crystals were added to a mixed solvent of 25 mL of tetrahydrofuran and 25 mL of methanol and stirred. 25 mL of 46.95 mM KOH aqueous solution was added and refluxed at 80 ° C for 12 h under air conditions. After cooling to room temperature, 50 mL of water was added and the mixture was heated to 80 ° C until the solid was completely dissolved. The pH was then adjusted to 6 with 1 M HCl, filtered, washed with water, and dried in vacuo to obtain a brown solid (Fe-TCPP).
[0111] Step 5: Take 0.05 mmol of the Fe-TCPP prepared above and add it to 20 mL of N,N-dimethylformamide, dissolve it by ultrasonication, and obtain solution A; put the surface-grown α-Fe 2 O 3 -450 FTO glass, drop 5mL solution A, react at 160℃ for 12h, cool to room temperature, take out the sample, put it into glassware filled with N,N-dimethylformamide and acetone, soak for 10min respectively, and vacuum dry to obtain α-Fe 2 O 3 @Fe-TCPP, denoted as Fe-TCPP-450.
[0112] Take 130mL Na 2 SO 4 , polyethylene glycol (PEG) mixed solution, wherein Na 2 SO 4 The concentration is 0.05M, and the concentration of PEG is 10mg / L. The platinum electrode is used as the counter electrode, the saturated Ag / AgCl electrode is used as the reference electrode, and the 3*1cm 2 The Fe-TCPP-450 thin film glass was used as the working electrode. At pH = 5, the current density was 5 mA / cm 2 The catalytic activity was tested under the conditions of xenon lamp (current 16A, filter 420nm). The experimental results showed that the degradation efficiency of the product on PEG solution was 70.1% within 4 hours.
[0113] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. An α-Fe2O3@MIL-141 metal organic framework composite material, characterized in that: The invention comprises a Ti-doped rod-shaped α-Fe2O3 nanoarray and MIL-141(Fe) in-situ coated on the surface of the array; wherein the organic ligand of the MIL-141(Fe) is tetrakis(4-carboxyphenyl)porphyrin.
2. The method for preparing the α-Fe2O3@MIL-141 metal organic framework composite material according to claim 1, characterized in that: The steps include: Step a, adding a soluble iron salt to an aqueous sodium sulfate solution, mixing evenly, to obtain a ferric chloride mixed solution; Add soluble titanium salt into anhydrous ethanol and mix well to obtain titanium chloride solution; Evenly mixing the ferric chloride mixed solution and the titanium chloride solution to obtain a precursor solution; Step b, adding the precursor solution and conductive glass into a hydrothermal reactor, reacting at 110° C. to 130° C. to form a Fe-OOH nanoarray on the conductive glass; calcining the Fe-OOH nanoarray at 400° C. to 500° C. to obtain a Fe2O3 nanoarray; Step c, dissolving tetrakis(4-carboxyphenyl)porphyrin in N,N-dimethylformamide, adding trifluoroacetic acid, and mixing well to obtain a tetrakis(4-carboxyphenyl)porphyrin solution; Step d, adding the Fe2O3 nanoarray and tetrakis(4-carboxyphenyl)porphyrin solution into a hydrothermal reactor, reacting at 160°C to 180°C to obtain an α-Fe2O3@MIL-141 metal organic framework composite material.
3. The method for preparing the α-Fe2O3@MIL-141 metal organic framework composite material according to claim 2, characterized in that: In step a, the soluble iron salt is ferric chloride; and / or In step a, the soluble titanium salt is titanium tetrachloride.
4. The method for preparing the α-Fe2O3@MIL-141 metal organic framework composite material according to claim 2, characterized in that: In step a, the molar ratio of the soluble iron salt to sodium sulfate is (0.5-2):(0.5-2); and / or In step a, the ratio of sodium sulfate to water in the sodium sulfate aqueous solution is (0.5-2) mmol: (8-12) mL; and / or In step a, the ratio of the soluble titanium salt to anhydrous ethanol is (0.5-2) mmol: (15-25) mL; and / or In step a, the molar ratio of the soluble titanium salt to the soluble iron salt is (0.5-2):(0.5-2); and / or In step a, the volume ratio of the ferric chloride mixed solution to the titanium chloride solution is 1:(40-50).
5. The method for preparing the α-Fe2O3@MIL-141 metal organic framework composite material according to claim 2, characterized in that: In step b, the reaction time is 4h to 5h; and / or In step b, the calcination time is 2h to 3h.
6. The method for preparing the α-Fe2O3@MIL-141 metal organic framework composite material according to claim 2, characterized in that: In step c, the ratio of the tetrakis(4-carboxyphenyl)porphyrin solution to N,N-dimethylformamide is (0.04-0.06) mol: (15-25) mL; and / or In step c, the volume ratio of N,N-dimethylformamide to trifluoroacetic acid is (15-25):(0.4-0.6).
7. The method for preparing the α-Fe2O3@MIL-141 metal organic framework composite material according to claim 2, characterized in that: In step d, the reaction time is 12 h to 14 h.
8. Use of the α-Fe2O3@MIL-141 metal organic framework composite material according to claim 1 in photoelectrocatalytic degradation of polyethylene glycol.
9. A method for photoelectrocatalytic degradation of polyethylene glycol, characterized in that: The steps include: In a three-electrode system, the α-Fe2O3@MIL-141 metal organic framework composite material prepared by the preparation method of the α-Fe2O3@MIL-141 metal organic framework composite material according to any one of claims 2 to 8 is used as a working electrode to perform photoelectrocatalytic degradation of a solution containing polyethylene glycol.
10. The method for photoelectrocatalytic degradation of polyethylene glycol according to claim 9, characterized in that: The current density of the photoelectrocatalytic degradation is 4 mA / cm 2 ~6mA / cm 2 .